Circadian rest/activity rhythms in knee osteoarthritis with insomnia: A study of osteoarthritis patients and pain-free controls with insomnia or normal sleep. (March 2015) - Spira, Adam P.; Runko, Virginia T.; Finan, Patrick H.; Kaufmann, Christopher N.; Bounds, Sara C.; Liu, Lianqi; Buenaver, Luis F.; McCauley, Lea M.; Ancoli-Israel, Sonia; Smith, Michael T.
Abstract : Aberrant circadian rest/activity rhythms (RARs) may promote poor aging-related health outcomes. Osteoarthritis and chronic insomnia are common age-related conditions, but the circadian RARs of each group have not been well characterized or compared. We evaluated actigraphic RARs in individuals with: (1) knee osteoarthritis (KOA) only; (2) chronic insomnia only; (3) KOA + insomnia; and (4) pain-free good sleepers. Compared to participants with KOA only, those with KOA + insomnia had less robust RARs. There were no differences between other groups. Further research is needed to evaluate whether aberrant RARs contribute to arthritis symptoms and insomnia in KOA, and whether strengthening RARs ameliorates arthritis symptoms.